The inseparability between mother tongue and intellect progress - Rahmat Allah, Abdul Khaliq Fadl (Arab Journal for Sciences and Research Publishing, 2016)
The importance of this study appears in it is call for using Arabic language as a medium of instruction in teaching at all educational stages (level 5) and for all specialization, and its aims at pinpointing This scientific study aims at pinpointing the strong pond between scientific innovation and gripping on the reasons of evolution in all aspects of life and teaching of all different subjects in the mother tongue at all levels. The current scientific educational studies verified that man cannot be shown as creative in a complete way except when he sticks to his original mother tongue, and the vast majority of the world universities teach their subjects and the different specializations in their national languages whether this in the orient or in the west. The paper mentioned the experiments of each of Israel, China, and Malaysia which use their national languages as means of instruction in all educational levels and stages and their centers of researches, which lead the evolution of these in scientific domain and life in general. The paper also reflects on the number of the studies which are excited to a number of students and teachers who are specialized in different domains. The results of the studies have clearly shown that Arabic language is qualified to be a language of teaching for all subjects and specializations, at all educational stages and at the centers of researches (this is if we want to be a progressing nation scientifically, ideologically, and pioneering in all domains. The paper adopts the descriptive analytical approach, and it reaches a number of findings, some of which are: 1. The great link between language and the scientific system. 2. Learning in the mother tongue will accelerate or hasten understanding, consolidate comprehension, and deeply roots knowledge and saves time